Minimal surfaces in nuclear pasta with the time-dependent hartree-fock approach - Schuetrumpf, Bastian; Klatt, Michael; Iida, K.; Schröder-Turk, Gerd; Maruhn, J. A.; Mecke, Klaus; Reinhard, Paul-Gerhard (Proceedings of Science, 2014)
In continuation to the studies of the whole variety of pasta shapes in [1], we present here calculations performed with the Hartree-Fock and time-dependent Hartree- Fock method concerning the mid-density range of pasta shapes: The slab-like, connected rod-like (p-surface) and the gyroidal shapes. On the one hand we present simulations of the dynamic formation of these shapes at finite temperature. On the other hand we calculate the binding energies of these shapes for varying simulation box lengths and mean densities. All of these shapes are found to be at least metastable. The slab shape has a slightly lower energy because of the lack of curvature, but among these three configurations the gyroidal shape is metastable for the widest range in mean density.
CRIS-Team Scopus Importer:2023-07-24